Islam i Tromsø: en begynnelse på en historie - Bratsvedal, Ine Rolseth (Universitetet i Tromsø, 2013)
This thesis looks at how different people’s practices, surroundings and networks have shaped different expressions of Islam in Tromsø, from 1981 when the first Muslims arrived until March 2013. It is based on fieldwork consisting of interviews, participation in social events and the gathering of documents, including earlier research, newspapers and archive material. This is an attempt to write an history of Islam in Tromsø. The data presented in this history are discussed using theoretical frameworks from Christine M. Jacobsen (2011), Thomas A. Tweed (2006) and Manuel A. Vásquez (2011). These perspectives focus on movements, contexts and networks, and enable me to shed new light on my findings. Using Jacobsen’s ethnography (2011) and some of her theoretical perspectives, I try to put Islam in Tromsø in a Norwegian context by comparing my findings with research from other places in Norway. Using some of the perspectives of Tweed (2006) and Vásquez (2011), I look at how Muslims in Tromsø use Islam to build homes and orientate themselves in time and space. I also look at how networks contribute to shaping Muslim communities in Tromsø, including how they mark inclusion and exclusion, and how they create hierarchies. This thesis finds that Islam in Tromsø is established and continuously fashioned through people’s practices, surroundings and networks.